Ketamine for Migraine in the Emergency Department. (April 2020) - Bilhimer, Matthew H.; Groth, Meghan E.; Holmes, Ashley K.
Abstract : Ketamine is utilized often in the emergency department (ED) for rapid sequence intubation, procedural sedation, and acute pain management. The treatment of migraine headache in the ED varies widely and is dependent on several factors including migraine cause, previous successful abortive methods, and provider preference. Several medications are currently employed to treat acute migraine including nonsteroidal anti-inflammatory drugs, triptans, antihistamines, prochlorperazine, and corticosteroids, among others. Interest in ketamine as an abortive agent to treat migraine has increased as evidenced by recent studies evaluating its use in the ED. This review examines the data regarding the use of ketamine to treat migraine headache. The concept of treating migraine headache with ketamine has been studied for more than 20 years. Early studies conducted primarily in the outpatient setting evaluated ketamine through multiple routes of administration and differing migraine causes with varying results. These early data seem to suggest that ketamine provides relief from headache severity but provides little information regarding the optimal dose and route of administration. Recent active comparator and placebo-controlled trials in the ED utilizing subdissociative doses of ketamine (0.2–0.3 mg/kg intravenously) show conflicting results. To confound the decision regarding its use further, ED providers encounter differing recommendations regarding its place in therapy. Current data suggest that ketamine may provide pain relief to patients with migraine headache. Although there may be a role for ketamine in certain cases after more robust evidence becomes available, currently it is premature to incorporate ketamine into routine use. Several questions remain to be answered including its overall efficacy, place in therapy, dosage, and risk of undesirable side effects.